Naufrágios e outros infortúnios na História Trágico-Marítima da carreira da Índia (Séculos XVI e XVII) - kockel, Marcelo Fidelis [UNESP] (2014)
This research promotes a mapping on the reports about shipwrecks written in Portuguese - such reports mentions the trips on the route to India in XVIth and XVIIth centuries - and attempts to analyze the point of coexistence, tension and dialogue among traditional and bookish knowledge of ancient and middle age culture with the new modern attainment, more pragmatical and based on experience. The main assumption that leads our research is that the sea (which was, by that time, a space related to fear, to imaginary lands, to sea monsters, to abyss, and hellish figures) becomes related to the casualties experienced during a sea trip: the starvation, the thirstiness, the calmness, the diseases, the storms and mainly the shipwrecks. From this hypothesis, by mapping those reports, we parallelly search to know which was the usage and circulation of the analyzed writings on that matter among Portuguese society by that time, its author and its social position. Finally, we look for which conceptions about the life on board and on the sailed seas were being formulated. In other words, the analysis we now intend to do should be interpreted as a procedure that fundamentally aims to verify the forms in which the discourses cross mutually and establish its discursive regularities in series